2020
DOI: 10.3390/genes11080889
|View full text |Cite
|
Sign up to set email alerts
|

ICEs Are the Main Reservoirs of the Ciprofloxacin-Modifying crpP Gene in Pseudomonas aeruginosa

Abstract: The ciprofloxacin-modifying crpP gene was recently identified in a plasmid isolated from a Pseudomonas aeruginosa clinical isolate. Homologues of this gene were also identified in Escherichia coli, Klebsiella pneumoniae and Acinetobacter baumannii. We set out to explore the mobile elements involved in the acquisition and spread of this gene in publicly available and complete genomes of Pseudomonas spp. All Pseudomonas complete genomes were downloaded from NCBI’s Refseq library and were inspected for the presen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 43 publications
(68 reference statements)
2
13
0
Order By: Relevance
“…Although crpP was originally identified in plasmid pUM505 [2], ICEs were identified as a major reservoir of crpP genes in P. aeruginosa [14]. Our results revealed that all the fully sequenced crpP-carrying ICEs had the highly conserved 45-bp terminal attL/attR pairs and displayed similar backbone gene organizations, and thus were assigned into a newly identified Tn6786 family.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Although crpP was originally identified in plasmid pUM505 [2], ICEs were identified as a major reservoir of crpP genes in P. aeruginosa [14]. Our results revealed that all the fully sequenced crpP-carrying ICEs had the highly conserved 45-bp terminal attL/attR pairs and displayed similar backbone gene organizations, and thus were assigned into a newly identified Tn6786 family.…”
Section: Discussionmentioning
confidence: 82%
“…S1). Additionally, all these ICEs were integrated at the end of the tRNA Lys gene as described in a previous report [14].…”
Section: Prevalence Of Crpp Genes and Crpp-carrying Ices In Chinese P Aeruginosa Isolatesmentioning
confidence: 99%
See 1 more Smart Citation
“…crpP gene was first detected in 2018 as encoded within the pUM505 plasmid in a P. aeruginosa clinical isolate from Mexico [ 9 ]. Since then, ciprofloxacin-modifying crpP genes have been identified in P. aeruginosa as part of different mobile integrative and conjugative elements (ICEs) that frequently transfer horizontally [ 10 ]. However, homologous crpP genes have also been located in chromosomal pathogenicity genomic islands (PAGI) of P. aeruginosa clinical isolates recovered in France and Switzerland between 2000 and 2015 [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nearly half of the ICEs/IMEs carried at least one AMR gene (228/553), with the ciprofloxacin-modifying crpP gene and the sulphonamide-resistance sul1 gene being most frequent ( Table S13 ). Indeed, the crpP gene was recently shown to be widely dispersed across ICEs from P. aeruginosa (42). Around one third of the ICEs/IMEs (193/553) carried at least one defence system, resulting in a total of 250 defence systems across the ICEs/IMEs and including 27 different types ( Figure S10 and Table S13 ).…”
Section: Resultsmentioning
confidence: 99%